Monopoly without a monopolist: An economic analysis of the bitcoin payment system - Gur Huberman; Jacob D. Leshno; Ciamac Moallemi (Bank of Finland, 2017)
Owned by nobody and controlled by an almost immutable protocol the Bitcoin payment system is a platform with two main constituencies: users and profit seeking miners who maintain the system's infrastructure. The paper seeks to understand the economics of the system: How does the system raise revenue to pay for its infrastructure? How are usage fees determined? How much infrastructure is deployed? What are the implications of changing parameters in the protocol? A simplified economic model that captures the system's properties answers these questions. Transaction fees and infrastructure level are determined in an equilibrium of a congestion queueing game derived from the system's limited throughput. The system eliminates dead-weight loss from monopoly, but introduces other inefficiencies and requires congestion to raise revenue and fund infrastructure. We explore the future potential of such systems and provide design suggestions.
URN:NBN:fi:bof-201709051593
Keywords: D40; D20; L10; L50; 330